On Markovian Modeling of Vehicular Traffic Flow in Gwagwalada Metropolis, Nigeria. (MATEMATIKA, 2015)
Analysis of queue performance parameters is inevitable for efficient and effective congestion control and traffic free networking system. This study assesses the efficiency and effectiveness of road traffic systems, using the Atlas Hotel road intersection, Gwagwalada, Abuja Nigeria as a case study. Queue theory analytic methodologies are applied and parameters such as average arrival and service rate are calculated based on the data obtained at the said junction on daily basis for a period of one week. Inter-arrival time is 10 seconds and M/M/3 queue model was found appropriate. Considering the 15278 vehicles observed, major arrivals and departure were on the SDP leg, while the least arrivals and departure was witnessed on the Town-Hall leg, the El-Rufai and NITEL legs had varying degrees of arrivals and departure. Based on the data gathered, it was observed that the evenings record the highest magnitude of vehicular traffic at the intersection while mornings had the least.  It was concluded that with reference to the intersection studied, road traffic system performance within the Gwagwalada metropolis is stable as Level of Service is A with Average Control Delay(seconds/vehicle)  . Modernization and re-design of roadways, traffic education, as well as introduction of road traffic utilities were recommended.